2017
DOI: 10.20996/1819-6446-2017-13-3-370-377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sacubitril/Valsartan on Natriuresis, Diuresis and Blood Pressure in Hypertensive Patients

Abstract: Российский университет дружбы народов Россия, 117198, Москва, ул. Миклухо-Маклая, 6 Цель. Изучить влияние сакубитрил/валсартана по сравнению с валсартаном на натрийурез, диурез, артериальное давление (АД) и уровень биомаркеров у пациентов с артериальной гипертонией (АГ). Материал и методы. В двойном слепом рандомизированном перекрестном исследовании 16 пациентов с АГ получали сакубитрил/валсартан 400 мг 1 р/сут или валсартан 320 мг 1 р/сут в течение 7 дней. Изучена динамика 24-часового диуреза и натрийуреза… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Kobalava et al 26 performed an objective evaluation of natriuresis by measuring fractional sodium excretion and urinary cyclic guanosine monophosphate in hypertensive patients and compared it between valsartan and LCZ696. This study showed more effective natriuresis in patients on LCZ696 with a resultant reduced SBP and DBP.…”
Section: Discussionmentioning
confidence: 99%
“…Kobalava et al 26 performed an objective evaluation of natriuresis by measuring fractional sodium excretion and urinary cyclic guanosine monophosphate in hypertensive patients and compared it between valsartan and LCZ696. This study showed more effective natriuresis in patients on LCZ696 with a resultant reduced SBP and DBP.…”
Section: Discussionmentioning
confidence: 99%